Identification of Genetic Loci for Sugarcane Leaf Angle at Different Developmental Stages by Genome-Wide Association Study - Chen, Xinglong; Huang, Zhenghui; Fu, Danwen; Fang, Junteng; Zhang, Xiangbo; Feng, Xiaomin; Xie, Jinfang; Wu, Bin; Luo, Yiji; Zhu, Mingfeng; Qi, Yongwen (Frontiers in Plant Science, 2022)
Sugarcane (Saccharum spp.) is an efficient crop mainly used for sugar and bioethanol production. High yield and high sucrose of sugarcane is always the fundamental demands in sugarcane growth worldwide. Leaf angle and size of sugarcane can be attributed to planting density, which was associated with yield. In this study, we performed Genome-Wide Association Studies (GWAS) with a panel of 216 sugarcane core parents and their derived lines (natural population) to determine the genetic basis of leaf angle and key candidate genes at seedling, elongation and maturity stage. A total of 288 significant associated loci of sugarcane leaf angle at different developmental stages were identified by GWAS. Among them, one key locus and eleven loci was identified in all three stages and two stages, respectively. An InDel marker (SNP Ss6A_102766953) linked to narrow leaf angle was obtained. Overall, 4089 genes were located in the confidence interval of significant loci, among which 3892 genes were functionally annotated. Finally, thirteen core parents and their derivatives tagged with SNPs were selected for Marker-assisted selection (MAS). These candidate genes are mainly related to MYB transcription factors, auxin response factors, serine/threonine-protein kinases, etc. They are directly or indirectly associated with leaf angle in sugarcane. This research provided a large number of novel genetic resources for the improvement of leaf angles and simultaneously to high yield and high bioethanol production.